Shape-Memory Materials - Esther Ares, Alicia (IntechOpen, 2018)
Shape-memory materials are materials that react under variations of electric or magnetic fields, physical or chemical changes, and that when returning to the initial conditions recover their original form, capable of repeating this process an infinite number of times without deteriorating. The characteristics, fabrication techniques, and thermomechanical treatment of various shape-memory materials are described in detail in this book. The book describes several principles and applications.